PETRHA (Physioterapy E-Training Re-habilitación) - Ortega, María (2021)
PETRHA (Physiotherapy E-Training Re-HAbilitation), is an European project that is being developed since 2015 to 2017. His main goal is to develop a serious game for students in Physiotherapy. This simulation game will enhance the learning process of the "clinical approach in physiotheray" and will allow more intensive training opportunities for students in association with the use of simulation.